Association of the atherosclerosis, small vessel disease, cardioembolism, other causes with the executive function of the montreal cognitive assessment Indonesia in patients with post ischemic stroke - Hastani, Dwi Retno; Rambe, Aldy S.; Iqbal, Kiki M. (International Journal of Research in Medical Sciences, 2019)
Background: ASCO Phenotype classification is a new classification of stroke based on phenotypic system. ASCO classification can evaluate the etiology of ischemic stroke comprehensively to characterize patients using different grade of evidence for the subtype of ischemic stroke. ASCO classification can predict post ischemic stroke cognitive decline. This Study purpose to evaluate the association between ASCO classification with the executive function in post ischemic stroke patients. Methods: This cross sectional study followed by 28 post ischemic stroke patients (men 16, women 12) over 3 months. Mean age 52.82±8.66. Cognitive function was assessed by Montreal Cognitive Assessment Indonesia (MoCA INA). Results: There were 17 patients with grade 1 atherosclerosis (ASCO A1), ten patients with grade 1 small vessel disease (ASCO S1), one patient with grade 1 cardioembolism (ASCO C1) in post ischemic stroke. Grade 1 atherosclerosis (ASCO A1) was significantly associated with executive function decline (p=0.002), naming decline (p=0.05), abstraction decline (p=0.001), memory decline (p=0.002) and orientation decline (p=0.016)). Grade 1 small vessel disease (ASCO S1) was significantly associated with executive function decline (p=0.001) and memory decline (p = 0.001) and abstraction (p=0.001). Grade 1 cardioembolism 1 (ASCO C1) was not significantly associated with cognitive decline. Conclusions: There was significant association between ASCO classification with the executive function of Montreal Cognitive Assestment Indonesia (MoCA INA) in post ischemic stroke patients.